PENGARUH PERBANDINGAN MOLAR OKSIDA SiO2:Al2O3 dan Na2O:SiO2 TERHADAP SIFAT MEKANIK GEOPOLIMER BERBASIS LATERITE DEPOSIT BONE - Farina, Farina; Subaer, Subaer; Haris, Abdul (JFT : Jurnal Fisika dan Terapannya, 2019)
The main objective of this research is to determine the effect of molar oxides of SiO2:Al2O3 and Na2O:SiO2 to the mechanical properties of geopolymer based on laterite soil deposite Bone. Geopolymers were produced through alkali-activation method of dehydroxylation laterite. Dehydroxylation was performed by using high-temperature furnace at Â for 4 hours. The chemical compositions and the microstructure properties of the starting and the resulting materials were characterized based on X-Ray Diffraction (XRD) and Scanning Electron Microscopys (SEM). Measurements of bulk density, apparent porosity and compressive strength were carried out by using Archimedes method and Universal Testing Machine. The results showed that the highest phase of the starting material was quartz (SiO2). The physical properties of geopolymers was examined from the value of their bulk density, apparent porosity and the magnitude of their compressive strength. The results showed that the value of the porosity and the density are inversely proportional, the smaller the porosity, the greater the density. The highest compressive strength value was 6.33 MPa obtained from the sample designated as K6. It was found that geopolymer based on Bone laterite exhibited good mechanical properties.